2001
DOI: 10.1590/s0100-204x2001000900010
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutritivo da silagem de cana-de-açúcar tratada com uréia e acrescida de rolão-de-milho

Abstract: Resumo O objetivo deste trabalho foi determinar o valor nutritivo da silagem de cana-de-açúcar tratada com 0,5% de uréia e acrescida de 0, 40, 80 e 120 kg de rolão-de-milho/t de cana-de-açúcar picada e ensilada. O experimento foi desenvolvido no Instituto de Zootecnia, em Nova Odessa, SP, em delineamento de blocos completos ao acaso com quatro repetições. O teste de consumo e digestibilidade foi efetuado com ovelhas em gaiolas com coletor e separador de fezes e urina. O teste constou de três períodos de 10, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
26

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 5 publications
(3 reference statements)
2
6
0
26
Order By: Relevance
“…These results were predictable because of the higher yeast concentration in the silages with greater sugarcane proportions, as reported previously. The ethanol values of sugarcane silage alone were similar to those reported by other authors, with values ranging from 69 to 80 g/kg (Andrade et al, 2001;Bernardes et al, 2007;Pedroso et al, 2007). Losses through gases are very important at sugarcane silage because they are highly correlated to the ethanol content (903 g/kg) and to the dry matter recovery (893 g/kg) (Pedroso et al, 2007).…”
Section: Inoculantsupporting
confidence: 86%
“…These results were predictable because of the higher yeast concentration in the silages with greater sugarcane proportions, as reported previously. The ethanol values of sugarcane silage alone were similar to those reported by other authors, with values ranging from 69 to 80 g/kg (Andrade et al, 2001;Bernardes et al, 2007;Pedroso et al, 2007). Losses through gases are very important at sugarcane silage because they are highly correlated to the ethanol content (903 g/kg) and to the dry matter recovery (893 g/kg) (Pedroso et al, 2007).…”
Section: Inoculantsupporting
confidence: 86%
“…According to the tested contrasts, inoculation with these bacteria increased the final acetic acid concentration of the silages, so that the highest values were observed for the silages inoculated with L. brevis compared to those inoculated with L. buchneri. In the present study, the acetic acid concentrations in the silages inoculated with heterofermentative bacteria were equal to those found by Freitas et al (2006), who reported values between 2.6 and 4.5%, that were higher than those reported by Andrade et al (2001) and Pedroso et al (2007) who obtained values varying between 0.9 and 2.2% and of 1.93 to 2.9% for sugar cane with different additives.…”
Section: Resultssupporting
confidence: 47%
“…Values between 1.5 and 4.3% of this acid in the DM can be found in the literature (Alli et al, 1983;Alcântara et al, 1989;Andrade et al, 2001;Freitas et al, 2006). Pedroso et al (2007) reported values of 5.2 a 7.6 for sugar cane silages with different additives.…”
Section: Resultsmentioning
confidence: 86%
“…Para este tratamento, possivelmente houve maior digestibilidade aparente da MS, o que resulta em maior consumo, como descrito por Andrade et al (2001). Segundo Restle et al (2000), o maior consumo de MS associado à alta concentração energética das dietas implica aumento no consumo de ED.…”
Section: Resultsunclassified